(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The research aims to use electronic games in teaching the ’Geometric Shapes’ unit to enhance the geometric shapes classification skills of third-grade students at Abdullah bin Umar School in Unaizah. The study also aims to identify the appropriate method for employing electronic games in mathematics teaching. The researcher followed a procedural approach, with 27 students taught using electronic games and another 27 students taught using usual methods. To achieve the goal, the researcher selected educational electronic games through the Wordwall program to develop students’ skills in geometric shapes classification. The researcher prepared and administered a test to measure students’ skills in geometric shapes classification after the intervention for all students. Additionally, observation cards and interviews were used to collect information and data about students’ experiences with electronic games for reflective purposes. The research results showed that students in the experimental group who learned using electronic games achieved significantly better results in the geometric shapes classification test compared to the control group. The results also indicated that students in the experimental group demonstrated higher motivation and interest in learning compared to students in the control group. The study concludes by proposing practical recommendations for using electronic games in mathematics teaching for third-grade students. Based on these findings, the research provides relevant conclusions and reflective observations related to the utilization of electronic games in mathematics education.